Duch Ameryki Łacińskiej nadzieją dla (nie)chrześcijańskiej Europy - Marta Sienkiewicz, (Annales Missiologici Posnanienses, 2019)
The article indicates the disappearance of Christianity in Europe. The article refers to Christian hope as an inspiration and motivation to undertake evangelization activities. The article contains references to popes who see help for secularized Europe in Latin America and the people of this continent. The text emphasizes the importance of culture in experiencing religion and building relationships with God. It signals that re-evangelization is needed in modern Europe, which will lead to the rebuilding of Christian identity. The text also emphasizes that Christianity is a religion for everyone, and Christian teaching should be uniform.